Appetite For Self-destruction - "Knopper, Steve, 1969-" (New York)
Includes bibliographical references (p. 253-280) and index.
Keywords: MUSIC TRADE -- HISTORY.;SOUND RECORDING INDUSTRY -- HISTORY.;COMPACT DISC INDUSTRY -- HISTORY